Gravity packaging final waste recovery based on gravity separation and chemical imaging control. (February 2017) - Bonifazi, Giuseppe; Serranti, Silvia; Potenza, Fabio; Luciani, Valentina; Di Maio, Francesco
Highlights: Density separation technique based on Reflux Classifier. Analytical/control strategies set up to certify a low content of PVC in the final SRF. Products identification and classification by NIR HyperSpectral Imaging. NIR HyperSpectral Imaging utilized for recycled aggregates quality control strategies set up. Abstract: Plastic polymers are characterized by a high calorific value. Post-consumer plastic waste can be thus considered, in many cases, as a typical secondary solid fuels according to the European Commission directive on E nd o f W aste (EoW). In Europe the practice of incineration is considered one of the solutions for waste disposal waste, for energy recovery and, as a consequence, for the reduction of waste sent to landfill. A full characterization of these products represents the first step to profitably and correctly utilize them. Several techniques have been investigated in this paper in order to separate and characterize post-consumer plastic packaging waste fulfilling the previous goals, that is: gravity separation (i.e. Reflux Classifier), FT-IR spectroscopy, NIR H yper S pectral I maging (HSI) based techniques and calorimetric test. The study demonstrated as the proposed separation technique and the HyperSpectral NIR Imaging approach allow to separate and recognize the different polymers (i.e. PolyVinyl Chloride (PVC), PolyStyrene (PS), PolyEthylene (PE), PoliEtilene Tereftalato (PET), PolyPropylene (PP)) in order to maximize the removal of the PVC fraction from plastic waste and to perform the full quality control of the resulting products, can be profitably utilized to set up analytical/control strategies finalized to obtain a low content of PVC in the final S olid R ecovered F uel (SRF), thus enhancing SRF quality, increasing its value and reducing the "final waste".